2004
DOI: 10.1592/phco.24.8.803.36070
|View full text |Cite
|
Sign up to set email alerts
|

Meropenem Administered as a Prolonged Infusion to Treat Serious Gram‐Negative Central Nervous System Infections

Abstract: The treatment of gram-negative infection of the central nervous system (CNS) presents a clinical challenge due to antibiotic resistance and difficulties with penetration into the cerebrospinal fluid (CSF). Two patients with gram-negative CNS infections were treated successfully with high-dose, prolonged infusions of meropenem. The CSF meropenem concentrations exceeded the minimum inhibitory concentration of the pathogen for virtually the entire dosing interval in both cases. Our experience demonstrates that do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 17 publications
1
22
0
1
Order By: Relevance
“…Recently, as well as higher doses or increased daily frequency of administration, PIT has often been the preferred mode for carbapenem therapy in order to increase the %T [MIC while remaining within the limits of the drug solution stability constraints [9][10][11]23]. It was reported that prolonged infusion of meropenem for the treatment of central nervous system infections resulted in adequate exposure at the site of infection and a successful clinical response [9,12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, as well as higher doses or increased daily frequency of administration, PIT has often been the preferred mode for carbapenem therapy in order to increase the %T [MIC while remaining within the limits of the drug solution stability constraints [9][10][11]23]. It was reported that prolonged infusion of meropenem for the treatment of central nervous system infections resulted in adequate exposure at the site of infection and a successful clinical response [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…As compared with traditional 0.5 h infusion therapy (TIT), this dosing methodology increases the %T [MIC , while remaining within the limits of the drug solution stability constraints [9][10][11]. In fact, it was reported that prolonged infusion (more than 3 h) of meropenem for the treatment of central nervous system infections resulted in adequate exposure at the site of infection and a successful clinical response [9,12]. Furthermore, it was reported that prolonged (4 h) drip infusion of meropenem was useful for the improvement of clinical efficacy against life-threatening pneumonia [13].…”
Section: Introductionmentioning
confidence: 99%
“…When the carbapenems and piperacillin/tazobactam were given as an extended infusion lasting ≥3 hours or as a continuous infusion rather than with standard short-term infusion, clinical outcomes were improved [111]. Prolonged infusion of meropenem, each dose administered over 3 hours, may also be successful in treating resistant gram-negative infections [112].…”
Section: Once a Pathogen Ismentioning
confidence: 99%
“…The longer infusion time for meropenem in our case is certainly not a new concept; use of extended-infusion meropenem has been reported in at least 3 previous adult patients (aged 38, 54, and 61 years) for treatment of gram-negative meningitis. 13,14 All patients recovered, experienced no adverse effects, and experienced CSF meropenem concentrations that exceeded the MIC of the organisms nearly 100% of the time. Unfortunately, we did not have as many optimally timed CSF or serum concentrations as in previously reported cases, but we were still able to document optimized therapy.…”
Section: Discussionmentioning
confidence: 97%
“…Concentration determination occurred via quantitative bioassay in accordance with previous reports. 13,14 Serum concentration results are available in Table 3. Using standard pharmacokinetic calculations to manipulate the obtained serum concentrations, the patient's volume of distribution was approximately 0.21 L/kg which is similar to the 0.3 to 0.4 L/kg that has been reported previously.15,16 The patient's estimated elimination constant (ke), calculated from the 2 values collected after cessation of the infusion, was 0.77 h−1 which correlates with an elimination halflife (t1/2) of 54 minutes, which is consistent with what is reported in individuals >2 years of age.17 The patient's estimated meropenem trough concentration was 2.5 µg/mL, which correlates with a trough concentration in the CSF of 0.05 to 0.15 µg/mL using 2% to 6% CSF-blood penetration ratio as has been reported.9,17,18 The meropenem concentration at the end of the infusion was 50 µg/mL, indicating that the concentration throughout the 4-hour infusion most likely remained above the MIC during that time.…”
Section: Casementioning
confidence: 99%